2021
DOI: 10.1177/23337214211002404
|View full text |Cite
|
Sign up to set email alerts
|

Changes to Family Caregiving of Older Adults and Adults with Disabilities during COVID-19

Abstract: The strict restrictions to reduce the spread of COVID-19 have disrupted the lives of many at-risk people and their family caregivers. This study explored how family caregivers perceived that family caregiving had changed during COVID-19 and the strategies they used to cope with these changes. We conducted 52 semi-structured interviews with family caregivers of adults over age 65 or adults with disabilities and analyzed the data through an inductive thematic analysis. Caregivers perceived the largest COVID-19-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 12 publications
4
63
0
Order By: Relevance
“…For example, a recent qualitative study found that caregivers are reporting added challenges of caregiving during the pandemic, which included keeping connected with the care recipient and social supports, keeping care recipients occupied despite reduced social stimulation, and seeking support and services in new ways, primarily through technology. 43 However, not all informal caregivers had the financial and technological capabilities of seeking additional supports, which presents the potential for COVID-19 to widen further existing gender, racial/ethnic, socioeconomic, and geographic disparities among informal caregivers. A study comparing the experiences of rural caregivers to urban and suburban caregivers during the pandemic found that rural caregivers were more than twice as likely to report a substantial increase in caregiver burden due to COVID-19 than urban caregivers.…”
Section: Informal Caregiving During the Covid-19 Pandemicmentioning
confidence: 99%
“…For example, a recent qualitative study found that caregivers are reporting added challenges of caregiving during the pandemic, which included keeping connected with the care recipient and social supports, keeping care recipients occupied despite reduced social stimulation, and seeking support and services in new ways, primarily through technology. 43 However, not all informal caregivers had the financial and technological capabilities of seeking additional supports, which presents the potential for COVID-19 to widen further existing gender, racial/ethnic, socioeconomic, and geographic disparities among informal caregivers. A study comparing the experiences of rural caregivers to urban and suburban caregivers during the pandemic found that rural caregivers were more than twice as likely to report a substantial increase in caregiver burden due to COVID-19 than urban caregivers.…”
Section: Informal Caregiving During the Covid-19 Pandemicmentioning
confidence: 99%
“…While the pandemic-specific challenges and support items developed for the National Poll on Healthy Aging are not an exhaustive list of all challenges or enhanced supports caregivers experienced during the pandemic, they do align with themes from recent in-depth qualitative interviews conducted with family caregivers during the pandemic. Lightfoot et al’s qualitative work found caregivers placed a new primary focus on safety and prevention of exposure, for example, which changed the caregiving role and responsibilities ( Lightfoot, Moone et al, 2021 ; Lightfoot, Yun et al, 2021 ). Additionally, as examined in our study, they found less availability of supports and services and reduced social contacts and isolation to be common pandemic care challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The poll format utilizes brief items with simple response scales across multiple domains. The caregiving measures described below stem from this measurement perspective and align with emerging qualitative work on challenges caregivers encountered during the COVID-19 pandemic ( Lightfoot, Moone et al, 2021 ; Lightfoot, Yun et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing such care would typically take up a substantial amount of time, and going to work may offer these workers some respite that would no longer be available if they were to telecommute. In addition, attendance at nursery schools and elderly care facilities was likely interrupted during the COVID-19 pandemic, 2025 making such care impossible to avoid while telecommuting.…”
Section: Discussionmentioning
confidence: 99%